THE EFFECT OF SERVICE QUALITY AND PROMOTION ON DANA CUSTOMER SATISFACTION AT FEB UNSRAT STUDENTS - Tampemawa, Varelino Syalom Justicio; Saerang, David Paul Elia; Tumewu, Ferdinand Johanis (Universitas Sam Ratulangi, 2024)
This study aims to determine the effect of service quality and promotion on Dana customer satisfaction of FEB UNSRAT students at Sam Ratulangi University. The study was conducted using a questionnaire that has spread to the customers on FEB students. The results revealed that the quality of accommodation, quality of accessibility, venue, and their dimensions contribute directly to satisfaction of tourists, their intention to return and eventually development of tourism industry in a region which should be considered highly by managers of tourist industry. The research results showed that service quality has a significant and positive effect on DANA Customer Satisfaction. Service quality is the most important factor that affects the satisfaction of customers. Keywords: Service quality, Promotion, Customer Satisfaction